Surgical technique for secondary pectoralis major transfer after reverse total shoulder arthroplasty to treat residual internal rotation dysfunction - Chang Hee Baek; Bo Taek Kim; Jung Gon Kim (Clinics in Shoulder and Elbow)
Reverse total shoulder arthroplasty (RSA) has emerged as a promising treatment option for rotator cuff tear arthropathy. However, concerns persist regarding horizontal rotational dysfunction after RSA. While many studies focus on improving external rotation after RSA, limited attention has been paid to internal rotation. In this technical note, we describe how to perform secondary pectoralis major transfer in a patient with residual internal rotation dysfunction after RSA.